The disruption of the traditional automotive business model and the acceleration toward sustainable mobility in France - Tharan, Laëtitia (My University, 2025)
The automotive industry has been an economic mainstay for hundreds of years and is now un- dergoing major transformations. This study explores how new entrants to the automotive mar- ket, such as Tesla and BYD are disrupting the business models of traditional manufacturers and accelerating the transition to more sustainable mobility in France. Historically, the automotive market was based on the mass production of internal combustion vehicles, with Toyota, Ford, Renault, and Volkswagen as the main players. However, the emergence of new, innovative play- ers from the technology sector is shaking up the market. Tesla and BYD, as new entrants, are introducing disruptive innovations to the market in the fields of electromobility, connectivity, autonomous driving, and mobility services. The arrival of new entrants and their innovations is challenging the practices and business models of the traditional manufacturers. New entrants have business models that focus on use rather than ownership, offering more sustainable mo- bility solutions and connected service platforms that meet new consumer expectations and en- vironmental goals. The study is based on qualitative data, using semi-structured interviews with professionals from the automotive sector in France to gather primary data. The interviews re- vealed a unanimous perception of new entrants as innovation, customer relationships, and au- tomotive value perception. Their disruptive innovations in battery technology and vehicle con- nectivity, meeting environmental goals and a mobility more sustainable for consumers, are forc- ing traditional automakers to react quickly to remain competitive in the French car market. The study shows that new entrants are having a significant impact on the French automotive market. The introduction of cutting-edge technology and innovative business models is forcing tradi- tional automakers to rethink their strategies. Traditional automakers are responding to these disruptions by implementing new strategies, investing more in electrification and connectivity technologies, as well as in their batteries and new green fuels. These changes are essential if traditional automakers want to remain competitive and continue to meet consumer expecta- tions and environmental regulations. In conclusion, the study highlights the profound changes taking place in the French automotive market as a result of the impact of new entrants. Tradi- tional automakers started to implement changes in their business model to become more flexi- ble and integrate technological innovations and electrification into their strategies. Their invest- ment in these more sustainable technologies and rethinking their model enables them to meet the environmental expectations of governments and consumers, ensuring continued value cre- ation in the fast-changing French automotive market.
Keywords: business models; automobile industry; electrification; innovations; combustion engines; electric vehicles; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business